Recruitment of Orc6l, a dormant maternal mRNA in mouse oocytes, is essential for DNA replication in 1-cell embryos - Murai, Shin (2010)
Mouse oocytes acquire the ability to replicate DNA during meiotic maturation, presumably to ensure that DNA replication does not occur precociously between MI and MII and only after fertilization. Acquisition of DNA replication competence requires protein synthesis, but the identity of the proteins required for DNA replication is poorly described. In Xenopus, the only component missing for DNA replication competence is CDC6, which is synthesized from a dormant maternal mRNA recruited during oocyte maturation, and a similar situation also occurs during mouse oocyte maturation. We report that ORC6L is another component required for acquisition of DNA replication competence that is absent in mouse oocytes. The dormant maternal Orc6l mRNA is recruited during maturation via a CPE present in its 3␣ UTR. RNAi-mediated ablation of maternal Orc6l mRNA prevents the maturation-associated increase in ORC6L protein and inhibits DNA replication in 1-cell embryos. These results suggest that mammalian oocytes have more complex mecha- nisms to establish DNA replication competence when compared to their Xenopus counterparts.